2013
DOI: 10.1021/ml400015f
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Optimization of an Aminoalcohol-Carbazole Series with Antimalarial Properties

Abstract: Recent observations on the emergence of artemisinin resistant parasites have highlighted the need for new antimalarial treatments. An HTS campaign led to the identification of the 1-(1-aminopropan-2-ol)carbazole analogues as potent hits against Plasmodium falciparum K1 strain. The SAR study and optimization of early ADME and physicochemical properties direct us to the selection of a late lead compound that shows good efficacy when orally administrated in the in vivo P. berghei mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…However, the Plasmodium falciparum strains are the most deadly. Some crude root extracts of the Clausena harmandiana show antiplasmodial activity against these strains due to presence of carbazole compounds [37]. As in the case of antibiotics, drug resistance of certain strains was observed also for well-known antimalarial drugs (e.g., chloroquine 17, Fig.…”
Section: Antimicrobial Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…However, the Plasmodium falciparum strains are the most deadly. Some crude root extracts of the Clausena harmandiana show antiplasmodial activity against these strains due to presence of carbazole compounds [37]. As in the case of antibiotics, drug resistance of certain strains was observed also for well-known antimalarial drugs (e.g., chloroquine 17, Fig.…”
Section: Antimicrobial Activitymentioning
confidence: 96%
“…Therefore, Tropical Diseases Research e the World Health Organization dependent institution, began collaboration with public and private sectors to screen several thousand compounds. Among them, the commercially available compound TDR30137 18 related to N-substituted carbazoles showed excellent activity (IC 50 ¼ 57 nM) in in vitro screen against the chloroquineresistant P. falciparum K1 (Pf-K1) in human red blood cells [37]. However, in vivo tests using the Plasmodium berghei mouse model compound didn't show any activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…1 Ha nd 13 CNMR spectra were recorded on aB ruker AM-400 spectrometer (400 MHz). Chemical shifts (d)a re given in ppm relative to TMS as internal standard, and signals are denoted with the following abbreviations:s ,s inglet; General procedures for the synthesis of carbazole aminoalcohols (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18):T oas olution of 9-(oxiran-2-ylmethyl)-9H-carbazole (2a-c,2mmol) in EtOH (20 mL), corresponding amines (6 mmol) was added. For low reactive amines (e.g.,a rylamines), BiCl 3 (1 mmol) was also added.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] However,f ew studies have addressed the relationships between topo Ia nd carbazoles. [17] More generally for carbazole compounds, carbazole aminoalcohols have been reported as potential antimalarial agents [18] and neurologicalr egulators, [19] while their antitumor capacity is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, further assay results indicated that JFD03612SC exhibited moderate antiplasmodial activity against P. falciparum 3D7 strain (IC 50  = 2.671 μM, BTB12253SC was not tested). Carbazole occurs in a wide-range of biologically active compounds, including antivirals (Yamada et al., 2012), antibiotics (Hurley et al., 2015), antiplasmodials (Molette et al., 2013). In addition, the aminoalcohol functional group was considered as a privileged structure for antischistosomal activity (Keiser et al., 2009).…”
Section: Introductionmentioning
confidence: 99%